2017
DOI: 10.26226/morressier.587e1051a874c6002655a272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of the lipoxygenase inhibitor baicalein on muscles in ovariectomized rats

Abstract: Sarcopenia, a loss of muscle mass accompanying osteoporosis, leads to falls and fall-related injuries. Baicalein, as a phytochemical agent, has an antioxidative and anti-inflammatory effect in muscle. In this study, sixty-one female Sprague Dawley rats were divided into five groups: four groups were ovariectomized (OVX) and one control group was nonovariectomized (NON-OVX). Eight weeks after ovariectomy, three disparate concentrations (1 mg/kg body weight (BW), 10 mg/kg BW, and 100 mg/kg BW) of baicalein were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
2
0
3
Order By: Relevance
“…It was observed that there was the formation of ramifications and intercommunications along the junction with a reduction in invagination and evagination lengths by 35% and 14.3%, respectively. According to Saul et al (), after the surgical procedure of ovariectomy in the muscle tissue, there is a decrease in density of the myofilament bundles of the muscle cell capable of triggering many deleterious effects in the muscle tissue homeostasis, and consequently, responses because of low sex hormones estrogen and progesterone. According to Campbell and Febbraio (), estrogen and progesterone in smaller proportions promote the capture and storage of glycogen in muscle tissue especially in muscles with type I fibers, and during physical activity, it preserves glycogen stores.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that there was the formation of ramifications and intercommunications along the junction with a reduction in invagination and evagination lengths by 35% and 14.3%, respectively. According to Saul et al (), after the surgical procedure of ovariectomy in the muscle tissue, there is a decrease in density of the myofilament bundles of the muscle cell capable of triggering many deleterious effects in the muscle tissue homeostasis, and consequently, responses because of low sex hormones estrogen and progesterone. According to Campbell and Febbraio (), estrogen and progesterone in smaller proportions promote the capture and storage of glycogen in muscle tissue especially in muscles with type I fibers, and during physical activity, it preserves glycogen stores.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genetic ablation of Alox5 failed to protect against muscle atrophy caused by denervation, whereas ablation of Alox12 or Alox15 was effective [7]. These results were supported by a report that baicalein, a phytochemical agent that also inhibits Alox12 and Alox15, maintained muscle fiber type and cross sectional area in ovariectomized rats [8]. Alox5 knockout in a model of post-menopausal osteoporosis produced increased skeletal muscle regenerative capacity after surgical injury, although this is distinct from the prevention of muscle fiber atrophy, which is characterized by dysregulated protein homeostasis and autophagy, and the preferential loss of particular myofiber types [9].…”
Section: Introductionmentioning
confidence: 80%
“…Eine daraufhin getestete Therapie mit einem oralen Lipoxygenaseinhibitor konnte zu einem signifikanten Anstieg der Knochendichte und der biomechanischen Stabilität führen und so aufzeigen, dass eine medikamentöse Lipoxygenaseinhibition ein vielversprechender Ansatz in der Osteoporoseprävention sein kann (Klein et al 2004). Saul et al (2016) und Kling (2016) Die histologische Struktur ist sowohl in der Kompakta als auch in der Spongiosa gleich (Welsch 2010).…”
Section: Zielsetzungunclassified
“…Auch die bereits in der Studie von Komrakova et al (2013) festgestellte Tatsache, dass osteoporotische Umbauprozesse mehr die spongiösen als die kortikalen Knochenanteile betreffen, konnte mittels 2D-Trabekelanalyse bestätigt werden. Eine etwaige Baicalein-Wirkung auf den osteoporotischen Wirbelkörper der Ratten konnte in dieser Studie nicht gänzlich belegt werden.Interessanterweise zeigte sich in einer weiteren Studie, dass Baicalein insbesondere in der maximalen Dosierung von 100 mg einen deutlich positiven Effekt auf die Angiogenese im Muskel der ovariektomierten Ratte besitzt und so die in der Literatur häufig beschriebene, durch östrogenmangel-induzierte Dekapillarisierung und Atrophie der Muskelfasern signifikant zu hemmen scheint(Kling 2016, Saul et al 2016. Einen deutlich positiven Effekt scheint Baicalein auf die kortikale BMD zu haben: Alle Baicalein-Gruppen wiesen signifikant höhere Werte gegenüber der OVX-Gruppe auf.…”
unclassified
See 1 more Smart Citation